1
$\begingroup$

In "Introduction to Calculus and Analysis" pages 221-223 Courant derives the following for an implicit function F(x,y)=0. Using

$dF = F_x dx + F_y dy = 0$

$dy = \frac{dy}{dx} dx = -\frac{F_x}{F_y}dx$

Also $y' = -\frac{F_x}{F_y}$

He says $f(x) = y$ therefore

$y' = \frac{F_x(x,f(x))}{F_y(x,f(x))}$

What I don't understand is, when I derived $y''$ using the Quotient Rule

$y'' = -\frac{F_yF_{xx}f' - F_xF_{yx}f'}{F_y^2}$

in the book however the result is

$y'' = - \frac{F_yF_{xx}+F_yF_{xy}f' - F_x F_{xy} - F_x F_{yy}f'}{F_y^2}$

I dont understand how the extra terms were derived.

Thanks,

$\endgroup$
1
$\begingroup$

It is just the Chain Rule. When deriving the numerator with respect to $x$ we get: $$ \frac{\partial}{\partial x}F_x(x,f(x))=\frac{\partial F_x}{\partial x}(x,f(x))+\frac{\partial F_x}{\partial y}\frac{df}{dx}=F_{xx}(x,f(x))+F_{xy}(x,f(x))f'(x). $$ Similarly, $$ \frac{\partial}{\partial x}F_y(x,f(x))=F_{xy}(x,f(x))+F_{yy}(x,f(x))f'(x). $$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.